Bacterial adhesion on conventional and self-ligating metallic brackets after surface treatment with plasma-polymerized hexamethyldisiloxane - Rogerio Amaral Tupinambá; Cristiane Aparecida de Assis Claro; Cristiane Aparecida Pereira; Celestino José Prudente Nobrega; Ana Paula Rosifini Alves Claro
ABSTRACT Introduction: Plasma-polymerized film deposition was created to modify metallic orthodontic brackets surface properties in order to inhibit bacterial adhesion. Methods: Hexamethyldisiloxane (HMDSO) polymer films were deposited on conventional (n = 10) and self-ligating (n = 10) stainless steel orthodontic brackets using the Plasma-Enhanced Chemical Vapor Deposition (PECVD) radio frequency technique. The samples were divided into two groups according to the kind of bracket and two subgroups after surface treatment. Scanning Electron Microscopy (SEM) analysis was performed to assess the presence of bacterial adhesion over samples surfaces (slot and wings region) and film layer integrity. Surface roughness was assessed by Confocal Interferometry (CI) and surface wettability, by goniometry. For bacterial adhesion analysis, samples were exposed for 72 hours to a Streptococcus mutans solution for biofilm formation. The values obtained for surface roughness were analyzed using the Mann-Whitney test while biofilm adhesion were assessed by Kruskal-Wallis and SNK test. Results: Significant statistical differences (p< 0.05) for surface roughness and bacterial adhesion reduction were observed on conventional brackets after surface treatment and between conventional and self-ligating brackets; no significant statistical differences were observed between self-ligating groups (p> 0.05). Conclusion: Plasma-polymerized film deposition was only effective on reducing surface roughness and bacterial adhesion in conventional brackets. It was also noted that conventional brackets showed lower biofilm adhesion than self-ligating brackets despite the absence of film.